Embelin Protects Against Acute Pentylenetetrazole-Induced Seizures and Positively Modulates Cognitive Function in Adult Zebrafish - Kundap, Uday Praful; Choo, Brandon Kar Meng; Kumari, Yatinesh; Ahmed, Nafees; Othman, Iekhsan Bin; Shaikh, Mohd Farooq (Frontiers in Pharmacology, 2019)
Purpose of the research: Epilepsy is a continuous process of neurodegeneration categorized by an enduring tendency to generate uncontrolled electrical firing known as seizures causing involuntary movement all over the body. Cognitive impairment and behavioral disturbances are among the more alarming co-morbidities of epilepsy. Anti-epileptic drugs (AEDs) were found to be successful in controlling epilepsy but are reported to worsen cognitive status in patients. Embelin (EMB) is a benzoquinone derived from the plant Embelia ribes and is reported to have central nervous system (CNS) activity. This study aims to evaluate the effectiveness of EMB against pentylenetetrazole (PTZ) induced acute seizures and its associated cognitive dysfunction. This was done via docking studies as well as evaluating neurotransmitter and gene expression in the zebrafish brain. The principal results: Behavioral observations showed that EMB reduced epileptic seizures and the T-maze study revealed that EMB improved the cognitive function of the fish. The docking study of EMB showed a higher affinity toward gamma-aminobutyric acid (GABAA) receptor as compared to the standard diazepam, raising the possibility of EMB working via the alpha subunit of the GABA receptor. EMB was found to modulate several genes, neurotransmitters, and also neuronal growth, all of which play an important role in improving cognitive status after epileptic seizures. Healthy zebrafish treated with EMB alone were found to have no behavioral and biochemical interference or side effects. The immunohistochemistry data suggested that EMB also promotes neuronal protection and neuronal migration in zebrafish brains. Major Conclusions: It was perceived that EMB suppresses seizure-like behavior via GABAA receptor pathway and has a positive impact on cognitive functions. The observed effect was supported by docking study, T-maze behavior, neurotransmitter and gene expression levels, and immunohistology study. The apparatus such as the T-maze and seizure scoring behavior tank were found to be a straightforward technique to score seizure and test learning ability after acute epileptic seizures. These research findings suggest that EMB could be a promising molecule for epilepsy induced learning and memory dysfunction.